Increasing substance use disorder counselors' self-efficacy and skills in talking to patients about sex and HIV risk: A randomized training trial. (1st June 2019) - Hatch-Maillette, Mary A.; Harwick, Robin; Baer, John S.; Wells, Elizabeth A.; Masters, Tatiana; Robinson, Audra; Cloud, Kasie; Peavy, Michelle; Wiest, Katharina; Wright, Lynette; Dillon, Kathleen; Beadnell, Blair
Highlights: SUD counselor training improves confidence and skill in discussing patient sex risk. An 8-hr skills-based training is superior to a 2-hr informational training. Counselor self-efficacy and skill improvement are maintained at 3-month follow up. Abstract: Background: People with substance use disorder (SUD) experience increased risk for HIV, Hepatitis C, and sexually transmitted illnesses via risky sex. This high-risk population would benefit from sexual risk reduction interventions integrated into SUD treatment. However, many SUD counselors report lack of skill or confidence in addressing sexual risk with patients. Methods: This study was part of a larger nested 2 × 2 factorial repeated measures design, which compared two levels of counselor training (Basic-2 h versus Enhanced-10 h plus ongoing coaching). We determined whether counselors receiving Enhanced training addressing their motivation, confidence and skills (a) increased knowledge about sexual issues; (b) increased self-efficacy to discuss sex with patients; and (c) improved skills in discussing sex as part of SUD treatment, compared with those receiving shorter information-based training. Counselors providing individual therapy at two opioid treatment programs (OTP) and two psychosocial outpatient programs in the United States were eligible. Randomization occurred after Basic training. Measures included self-report (self-efficacy and knowledge) and blinded coding of standardized patient interviews (skill). Results: Counselors receiving Enhanced training (n = 28) showed significant improvements compared to their Basic training counterparts (n = 32) in self-efficacy, use of reflections, and use of decision-making and communication strategies with standardized patients. These improvements were maintained from post-training to 3-month follow-up. No adverse effects of study participation were reported. Conclusions: Results suggest that counselors can improve their knowledge, self-efficacy and skill related to sexual risk conversations with patients based on modest skills-based training.